Propriedade intelectual e geneticamente variedades vegetais modificadas: análise dos contratos das empresas fornecedoras de sementes e do REsp 1.610.728/RS do Superior Tribunal de Justiça - SILVA, Paulo Felipe França Ferreira da (2022)
The advent of modern biotechnology brought the possibility of inserting characteristics into living beings, through the transgenic process, which until then were not possible to obtain in nature through classical manipulations man made. The legislation started to recognize genetically modified living beings as inventions subject to patent protection, as is the case of transgenic plants, generating collisions with institutes that originally regulated matters relating to plant varieties, through the institute of overlapping. The present work aimed to analyze the protection institutes foreseen in the Plant Protection Law - nº 9.456/1997 and of biotechnology patents in the Industrial Property Law - nº 9.279/1996, in order to verify the occurrence of overlapping for the cases of genetically modified plant varieties and the position of the Superior Court of Justice when judging REsp 1,610,728/RS, and its impacts on the effectiveness of the plant variety protection legislation, with the consequent elaboration of a conclusive technical report for the Empresa Brasileira de Pesquisa Agropecuária (Embrapa). The methodology used was of qualitative nature, using bibliographic and documental research. For that, searches were made in the plant variety and patents databases in order to verify patents and plant variety registrations dealing with the same protection. After that, transfer contracts of seed technology involving patent and plant variety rights holders and rural producers and seed multipliers were analyzed. Subsequently, judicial precedents and the content of the process that gave origin to REsp 1,610,728/RS were analyzed. The analyzes carried out showed the occurrence of overlap between the institutes of plant variety and biotechnology patents, which was possible since the advent of current legislation on the subject. Furthermore, the decision of the Superior Court of Justice ended up ratifying a mitigation of the Plant Protection Law for transgenic plant varieties, making it innocuous for this specific type of plants, since the rights arising from biotechnology patents are privileged. Such mitigation resulted in an imbalance in the relations between patent holders and rural producers, with the withdrawal of rights provided for in the specific legislation on cultivars, especially the one to donate seeds for free and reserve seeds for their own use, requiring the adoption of measures by the actors of the seed market and the public power to generate a new rebalance of relations through public policies and legislative changes.